Employee Relation Practices and Organisational Performance in Nigeria (Journal of Management and Social Sciences, 2022)
The study seeks to determine the effect of employees’ relation practices on organizational performance, at Guaranty Trust Bank, Ilorin. A sample size of 91 respondents comprising of the Bank staff in Ilorin metropolis was chosen. The sampling technique employed in the study was simple random sampling technique. Multiple regression was used for data analysis. The results revealed that both recruitment & selection and promotion are relevant for organizational performance. The hypotheses tested showed that all the variables tested are significant. It was concluded that recruitment & selection and promotion had significant effect on organizational performance. The study therefore recommends that certain practices need to be adopted and improved upon regularly to maintain a cordial relationship with employees and also increase organizational performance.  Keywords    Employees, organisation, performance, Ilorin